Quality of eggs from Lohmann Brown Classic laying hens fed black soldier fly meal as substitute for soya bean. (8th January 2018) - Secci, G.; Bovera, F.; Nizza, S.; Baronti, N.; Gasco, L.; Conte, G.; Serra, A.; Bonelli, A.; Parisi, G.
Abstract : Soya bean is the main protein source in poultry feed but rising prices make an alternative protein source necessary. Insects, such as the black soldier fly ( Hermetia illucens ), may be an attractive solution for hens, although little information is available on their effect on egg quality. The present study aims to fill this gap by testing the effect of 100% replacement of soya bean with H. illucens larva meal in the diet of Lohmann Brown Classic laying hens for 21 weeks. At the end of the trial, the eggs were characterized for parameters such as weight, colour, proximate composition of albumen and yolk, and content of carotenoids, tocopherols and cholesterol. The fatty acid profile of yolks was also determined. Hens fed the insect-based diet produced eggs (HIM group) with a higher proportion of yolk than the group fed the soya bean-based diet (SBM group). HIM was associated with redder yolks (red index 5.63 v . 1.36) than SBM. HIM yolks were richer in γ -tocopherol (4.0 against 2.4 mg/kg), lutein (8.6 against 4.9 mg/kg), β -carotene (0.33 against 0.19 mg/kg) and total carotenoids (15 against 10.5 mg/kg) than SBM yolks. The fatty acid composition of HIM yolks was almost identical to that of SBM yolks. Finally, HIM yolks contained 11% less cholesterol than SBM yolks. These results suggest that H. illucens larva meal is a suitable total substitute for soya bean meal in the diet of Lohmann Brown Classic laying hens. A sustainable alternative to the plant protein source therefore seems feasible.